2017
DOI: 10.1016/j.eurpolymj.2016.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Sacrificial crystal templating of hyaluronic acid-based hydrogels

Abstract: 2016-11-03T14:11:40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 54 publications
(68 reference statements)
0
22
0
Order By: Relevance
“…The bulk mechanical properties of hydrogel scaffolds play a role in their performance in vivo, and rheological experiments show that the storage modulus, G', of not templated gels was ca. 100 Pa., by comparison with 0.1 Pa for urea templated gels or 0.6-8.5 Pa or potassium dihydrogen phosphate templated gels, respectively; 41 and therefore that templation offers a method of tuning the mechanics of the gels to suit a specific biological niche. 41 Moreover, we have previously shown that the not templated and templated hydrogels were non-cytotoxic towards fibroblasts and Schwann cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The bulk mechanical properties of hydrogel scaffolds play a role in their performance in vivo, and rheological experiments show that the storage modulus, G', of not templated gels was ca. 100 Pa., by comparison with 0.1 Pa for urea templated gels or 0.6-8.5 Pa or potassium dihydrogen phosphate templated gels, respectively; 41 and therefore that templation offers a method of tuning the mechanics of the gels to suit a specific biological niche. 41 Moreover, we have previously shown that the not templated and templated hydrogels were non-cytotoxic towards fibroblasts and Schwann cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…100 Pa., by comparison with 0.1 Pa for urea templated gels or 0.6-8.5 Pa or potassium dihydrogen phosphate templated gels, respectively; 41 and therefore that templation offers a method of tuning the mechanics of the gels to suit a specific biological niche. 41 Moreover, we have previously shown that the not templated and templated hydrogels were non-cytotoxic towards fibroblasts and Schwann cells in vitro. 41 NPCs are particularly interesting for neural tissue engineering applications, and with a view to the use of the hydrogels for such applications we investigated the growth of NPCs within the starburst-like voids in the potassium dihydrogen phosphate-templated hydrogels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations